Peningkatan Prestasi Belajar Siswa Dengan Metode Diskusi Pada Pembelajaran Agama Katolik Siswa SMPN-9 Palangka Raya - Kuriani Kuriani (Jurnal Ilmiah Kanderang Tingang, 2023)
This study aims to determine the increase in student learning outcomes and student achievement in the subject of Catholicism, namely in the subject of Jesus the Prayer using the discussion method at SMPN-9 Palangka Raya. This study used a Classroom Action Research (PTK) design. The subjects of this study were 10 students in class VII, class VIII, and class IX, at SMPN-9 Palangka Raya, academic year 2021/2022. This research instrument consists of two types, namely through observation of student and teacher activities, and tests of student learning outcomes. Assessment through a written test in the form of an essay, a total of 6 questions written test in the form of fields, a total of 5 questions, and a written test in the form of multiple choice, a total of 10 questions. Based on data on student achievement results, SMPN -9 Palangka Raya in the 2021/2022 Academic Year for the Catholic Religion subject, out of a total of 10 students consisting of 2 students in class VII, 5 students in class VIII, 3 students in class IX , based on the results of learning achievement in the initial test as many as 9 people still did not reach the Maximum Completeness Criteria, only 1 person who completed the average value of 55.5 or 10%, who completed classically, while in the action in cycle I, the average value 69 students who finished studying in cycle 1, totaling 7 students out of 10 students, classically the learning completeness has reached 70% of the number of students. Cycle II the average value of students is 72.5. There are 8 students who complete, classically it reaches 80% of 10 students and there are two students who have not finished. The results of student achievement in the final test with an average score of 85, or 100% of the 10 students who took the test, and from the results of learning achievement, it was concluded that the learning method used by the teacher in delivering learning material, was able to improve student achievement.